(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
Malaria is the world’s most parasitic disease endemic in about 100 developing countries. The search for new antimalarial drugs from natural products is necessitated by resistance of the parasites to known antimalarial agents. This study evaluated phytocmical composition and the in vitro antiplasmodial potentials of Ficus gnaphalocarpa stem bark and Ipomea fistulos leaf methanolic extracts obtained from two areas (one each from Argungu and Yauri emirates of Kebbi State, Nigeria ) . The air dried samples of Ficus gnaphalocarpa (miq) C.C. Beng (stem bark) and Ipomea fistulos L. (leaves) were extracted with methanol for seventy two hours. The crude extracts were tested against chloroquine resistant strain of Plasmodium berghei berghei (NK-65) in vitro in 96 well microplates under anaerobic condition. The data obtained were analyzed using one way ANOVA and Duncan multiple comparison test with SPSS version 20.0. There was significant (P<0.05) reduction in the number of parasitized cells relative to control. F. gnaphalocarpa exhibited higher activity of 92.81% and IC50 (11.85 mg) while I. fistulos recorded an activity of 66.70% and IC50 (36mg). The plant extracts used in this study presented antiplasmodial activity. Further studies on in vivo assay, toxicity, histopathology, isolation and purification is recommended for possible development of their bio-constituents into antiplasmodial agents.